Potential of Coconut Shell Liquid Smoke as a Natural Preservative for Tofu: A Study of Organoleptic Properties, Protein Content, and Ash Content - Hamka; Sitti Hadijah; Marwati; Eva Nurmarini; Laily Ulfiyah; Aries Alfian Prasetyo (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Tofu has a short shelf life, creating a demand for natural preservatives. This study evaluated the effect of coconut shell liquid smoke at 2%, 4%, and 6% concentrations on white tofu’s organoleptic qualities (color, aroma, texture) and proximate composition (protein and ash) over three days. Tofu was soaked in liquid smoke, then assessed by 15 panelists for sensory acceptance and tested in the lab for protein (Lowry method) and ash (dry ashing). Panelists generally liked the color, aroma, and texture, though aroma and texture declined over time. The highest protein content (1.45%) was seen on day one with 6% liquid smoke. Protein and ash levels did not meet Indonesian National Standard (SNI) 3142-2018. Results indicate coconut shell liquid smoke shows promise as a natural tofu preservative, but concentration and application need optimization to improve nutritional and sensory qualities to meet standards.